PEMETAAN AIR TANAH & KUALITAS AIR TANAH SEBAGAI PROGRAM KERJA KKN IST AKPRIND DI DUSUN WOJO BANTUL - Untung Joko Basuki; Imron Faiqi (DHARMA BAKTI, 2019)
Water for humans is a very important element in life. Good water quality and healthy should be a concern for the community. Water quality is not only seen in terms of color and odor but also must be avoided from other elements that can endanger life. Ground water as one of the most widely used water sources should always be monitored from the quality side. As a real working college program and as a form of dedication to the community of KKN IST AKPRIND team in Wojo Sub-village, Sewon sub-district, Bantul district mapped groundwater and groundwater quality. The results of the survey are presented in the community, especially the RT in Wojo and provide several solutions to improve water quality. The groundwater mapping process is carried out by taking samples and testing groundwater quality in the laboratory to see iron content, turbidity, lead and e-coli.